ESSENCE OF THE INNOVATIVE PROCESSES IN THE ACTIVITY OF AGRICULTURAL ENTERPRISES - Hnatyshyn Л.; Khanas В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article outlines the essence, importance, and consequences of innovative processes. It is emphasized that innovative processes in the activities of agricultural enterprises are closely related to the processes of biological transformation in crop and animal husbandry and are oriented towards a long-term perspective. The spread of innovative processes in the environment of agricultural enterprises depends on the level of their innovative activity. The differences between the concepts of "innovative activity" and "innovative process" are considered. It is noted that innovative activity is a set of innovative processes aimed at creating, patenting, and spreading innovations. Agricultural enterprises are not characterized by innovative activity due to tax restrictions. They implement innovations within the framework of innovation processes, which are characterized by a qualitative change (modernization) of agricultural products and services, or the creation of a qualitatively new product. Innovative processes are revealed in the improvement or generation of new methods, approaches, and principles of operational activity of agricultural enterprises based on the use of new knowledge. Innovative processes in the activity of agricultural enterprises are manifested in the achieved competitive advantages, that is, the presence of some exclusive value in the supply to consumers, which provides prerogatives to a specific enterprise over competitors. Innovative activities of agricultural enterprises result in economic, ecological, and social effects. A special tool to activate innovative processes in the activities of agricultural enterprises is the value chain, which serves as the basis for creating added value for the product. The value chain of an agricultural enterprise consists of specific processes (innovation processes), which often go beyond internal production, and include a set of tangible and intangible costs that form the main and added value. Innovative processes in the activities of agricultural enterprises pave the way to rational, economical, and effective use of the resource component of production potential, as well as a tool for achieving a strategic goal.